Study on Diesel-Methanol-Water Emulsion Spray in High-Pressure Bomb - Wu, Dongyin; Wang, Wuqiang; Li, Chao; Wang, Yuhao; Shen, Qi; Yan, Junjie (Asian Journal of Chemistry, 2014)
The spray characteristics of diesel-methanol-water emulsion in a constant volume chamber were studied through high-speed photography experiment and the spray penetration and spray cone angle of emulsion in different ambient pressures and injection pressures were measured. The results showed that the spray penetration of diesel-methanol-water emulsion decreased with the increasing ambient pressure, but increased with the increasing nozzle pressure. The spray cone angle increased with the increasing the ambient pressure and the nozzle pressure. Under the same condition, the spray penetration of diesel-methanol-water emulsion was greater than that of diesel, while the spray cone angle was less than that of diesel. Because the viscosity and surface tension of diesel-methanol-water emulsion was greater than that of diesel, emulsion had worse atomization than diesel.